Community‐based traffic preservation in telecommunication networks1. (2nd December 2013) - Torres‐Padrosa, Víctor; Manzano, Marc; Calle, Eusebi; Marzo, Josep L.
Summary Large‐scale failures in telecommunication networks have been traditionally mitigated by attempting to preserve global connectivity in the network. However, although communication inside communities may be of high relevance, their preservation is a challenging task. To achieve this, we propose a new concept of community that combines not only the topological information of the network but also the traffic‐level interaction. This new concept is then used to present six novel community‐based strategies that, when working within a limited budget, are able to determine which are the best candidate nodes to protect. The strategies proposed have been tested over four different types of networks and have been compared with other well‐known immunization or protection methods. Results show that community‐based strategies better preserve the inner community traffic with respect to traditional approaches. Furthermore, in some cases, both global and intra‐community traffic preservation is able to be improved. Copyright © 2013 John Wiley & Sons, Ltd.